2002
DOI: 10.1021/om020106y
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of a Highly Crowded Cyclic Stannylene with Iodoalkanes, Enones, and Dienes. Inhibition of Nucleophilic Substitution at Tin(IV) Centers

Abstract: The cyclic stannylene RSnR (2; RR ) C(SiMe 3 ) 2 SiMe 2 CH 2 CH 2 Me 2 Si(Me 3 Si) 2 C) reacted with alkyl iodides R′I (R′ ) Et, i Pr) to give the Sn IV compounds RSnR′IR (6b,c), which were converted by treatment with silver trifluoroacetate into RSnR′(OCOCF 3 )R (7b,c). Reactions of the stannylene 2 with appropriate enones or diones yielded the products RRSnOC(Et)d CHCH 2 (10), RRSnOCPhdCPhO (11), RRSnOC 6 H 2 -3,5-t Bu 2 O (12), and RRSnOC 14 H 8 O (13) (OC 14 H 8 O ) 9,10-phenanthrenediolato). The crystal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 56 publications
3
29
0
Order By: Relevance
“…In the last 20 years, the phenomena described have included, for example, the low-coordinate bulky terphenyl ligand-decorated organometallics and analogs of acetylenes, highly silylated compounds, , various cyclic or acyclic metal amides, low-valent metal complexes containing heterocyclic or carbene ligands, the use of low-valent main-group metal species as ligands for transition-metal complexes or various areas of the activation of small molecules. , ,, In agreement with Lappert’s original observations, the possibility of the (co)-existence of both singlet and triplet states of tetrylenes (low-valent Group 14 metal (E) complexesR 2 E­(14)) , and even the aggregation of such molecules to the dimers–ditetrenes (R 2 E­(14)E­(14)­R 2 ) (Scheme ) by some authors described as heavier congeners of olefins have been observed many times both experimentally and theoretically. , It is believed that the sterical protection of the metal center is the reason for the existence of the monomeric tetrylene, and slightly controversially also for the excited-state stabilization (a triplet state) . According to several studies, the stabilization of the monomeric species R 2 E­(14) over the dimeric ones (R 2 E­(14)E­(14)­R 2 ) could be achieved not only by the steric properties of the metal substituents (even by cyclic silylated hydrocarbons), but also by the introduction of a heteroatom to the ligand skeleton, using π-electron-rich cyclic chelating ligands, the employment of an adjacent donor at...…”
Section: Introductionmentioning
confidence: 71%
“…In the last 20 years, the phenomena described have included, for example, the low-coordinate bulky terphenyl ligand-decorated organometallics and analogs of acetylenes, highly silylated compounds, , various cyclic or acyclic metal amides, low-valent metal complexes containing heterocyclic or carbene ligands, the use of low-valent main-group metal species as ligands for transition-metal complexes or various areas of the activation of small molecules. , ,, In agreement with Lappert’s original observations, the possibility of the (co)-existence of both singlet and triplet states of tetrylenes (low-valent Group 14 metal (E) complexesR 2 E­(14)) , and even the aggregation of such molecules to the dimers–ditetrenes (R 2 E­(14)E­(14)­R 2 ) (Scheme ) by some authors described as heavier congeners of olefins have been observed many times both experimentally and theoretically. , It is believed that the sterical protection of the metal center is the reason for the existence of the monomeric tetrylene, and slightly controversially also for the excited-state stabilization (a triplet state) . According to several studies, the stabilization of the monomeric species R 2 E­(14) over the dimeric ones (R 2 E­(14)E­(14)­R 2 ) could be achieved not only by the steric properties of the metal substituents (even by cyclic silylated hydrocarbons), but also by the introduction of a heteroatom to the ligand skeleton, using π-electron-rich cyclic chelating ligands, the employment of an adjacent donor at...…”
Section: Introductionmentioning
confidence: 71%
“…Whilst several stannanethiones and related compounds have now been isolated, these are typically stabilised either by intramolecular coordination of an amino substituent, 20 e.g. (15) are insufficiently bulky to prevent dimerisation. 22 In light of this, it is likely that the steric properties of the phosphine-borane-substituted alkyl ligands in 12 are insufficient to prevent dimerisation to the sulfur-bridged dimer [[(Me 3 Si){Me 2 P(BH 3 )}CH] 2 Sn(m 2 -S)] 2 (12a); however, on the available evidence it is not possible to distinguish between these two possibilities.…”
Section: Resultsmentioning
confidence: 99%
“…1,7,13-17 Several of the products of these reactions have been crystallographically characterised, including the products of the reactions of 4 (E = Sn) with ethyl iodide, ethyl vinyl ketone, and benzil. 15 Given the highly stabilising nature of the agostic-type interactions in 7, it was of significant interest to explore the reaction chemistry of this compound and to determine the extent to which these interactions might inhibit the reactivity of the electrondeficient tin(II) centre. This paper describes the reactions of 7 with a variety of substrates, including three sterically and electronically different alkyl halides, a dione, a diene, methanol and elemental sulfur.…”
mentioning
confidence: 99%
“…Analogously, treatment of 1 with an equimolar amount of chalcone ( E ‐benzylideneacetophenone) yielded 3 (52 %) (Scheme ). The solid‐state coordination geometry of 3 is similar to that of 2 (Figure 1 b), and the bond lengths and angles of the stannacycles in 2 and 3 are comparable to those of the benzil and ethyl vinyl ketone cycloadducts of a free stannylene, as reported by Eaborn, Smith, and co‐workers 7g. The diastereotopic hydride ligands in 3 , both located in the Fourier map with H⋅⋅⋅Sn distances of 2.37(4) and 2.46(4), resonate at −8.39 ( J SnH =91.1 Hz) and −8.84 ppm ( J SnH =149.6 Hz) in the 1 H NMR spectrum, reflecting chirality at the tin center.…”
Section: Methodsmentioning
confidence: 99%